2023
DOI: 10.3390/nu15040836
|View full text |Cite
|
Sign up to set email alerts
|

Untargeted Metabolomics Analysis Using UHPLC-Q-TOF/MS Reveals Metabolic Changes Associated with Hypertension in Children

Abstract: The mechanism of hypertension in children remains elusive. The objective of this study was to analyze plasma metabolomics characteristics to explore the potential mechanism of hypertension in children. Serum samples from 29 control children, 38 children with normal body mass index and simple hypertension (NBp), 8 children overweight with simple hypertension (OBp), 37 children with normal body mass index and H-type hypertension (NH) and 19 children overweight with H-type hypertension (OH) were analyzed by non-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 70 publications
0
2
0
Order By: Relevance
“…Notably, in a study on unique metabolomic characteristics related to cirrhosis mortality [ 36 ], 4-acetamidobutanoate significantly predicted mortality. It's reported that in patients with acute kidney injury (AKI), 4-acetamidobutanoate increased 12-fold [ 37 ], and its levels significantly increased in patients with morbid hypertension [ 38 ]. Similarly, alpha-hydroxyisovalerate, an organic acid related to branched-chain amino acid metabolism, has been linked with liver injury [ 39 ], diabetic nephropathy [ 40 ], and Maple Syrup Urine Disease [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Notably, in a study on unique metabolomic characteristics related to cirrhosis mortality [ 36 ], 4-acetamidobutanoate significantly predicted mortality. It's reported that in patients with acute kidney injury (AKI), 4-acetamidobutanoate increased 12-fold [ 37 ], and its levels significantly increased in patients with morbid hypertension [ 38 ]. Similarly, alpha-hydroxyisovalerate, an organic acid related to branched-chain amino acid metabolism, has been linked with liver injury [ 39 ], diabetic nephropathy [ 40 ], and Maple Syrup Urine Disease [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our results compare well with results of HILIC or derivatisation-GC–MS methods (Rakusanova et al, 2023 ; Zeki et al, 2020 ). For example, Zhang et al ( 2023 ) detected 755 positive ions in serum samples from 131 hypertensive children. The sample preparation required drying and reconstitution of the serum extract whereas our method involves a simple single extraction and centrifugation step, that can be completed within 15 minutes and immediately analysed.…”
Section: Discussionmentioning
confidence: 99%